Bioecología y manejo de Piezodorus guildinii (Hemíptera: Pentatomidae) en el cultivo de soya Glycine max - Campi Cadena, Isaac Bernabe (2025)
In Ecuador, soybean production is of great relevance and representativeness in the agricultural sector. However, in recent years it has not shown greater competitiveness due to the variety of insects that infest the plantations, which leads to the use of biosides that cause a detrimental effect on the environment and human health. It is recognized as the main insect that attacks soybean, Piezodorus guildinii, being of vital relevance for this crop. Research on the bioecology and control of P. guildinii in the soybean crop focused on discovering efficient and sustainable tactics for the management of this pest. The presence of the bug in soybean causes alterations in the phenological phase of seed filling, causing a slowdown in grain growth, deformation and discoloration of the grain, rapid maturation of the plant and ease of entry of disease-causing pathogens. The maximum amount of damage that occurs in the soybean crop occurs when there are between 2 and 3 bugs per plant. The strategies implemented for insect control, based on biological and cultural techniques, contribute to reduce the insect population naturally through crop rotation, the use of resistant varieties and the release of natural enemies (parasitoids). These methods are efficient and effective in the prevention and propagation of P. guildinii, as well as the relevance that these methods bring to the environment